2020
DOI: 10.1016/j.phro.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Focal salvage treatment for radiorecurrent prostate cancer: A magnetic resonance-guided stereotactic body radiotherapy versus high-dose-rate brachytherapy planning study

Abstract: Background and Purpose: Magnetic resonance imaging (MRI)-guided focal salvage high-dose-rate brachytherapy (FS-HDR-BT) is one of the treatment options for radiorecurrent localized prostate cancer. However, due to the invasive nature of the treatment, not all patients are eligible. Magnetic resonance linear accelerator (MR-Linac) systems open up new treatment possibilities and could potentially replace FS-HDR-BT treatment. We conducted a planning study to investigate the feasibility of delivering a single 19 Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In the CK plans with the synchrony tracking system, the CTV–PTV margin varied between 0 and 5 mm. MLC tracking on conventional linear accelerators was used in three studies [ 45 , 57 , 61 ]. A margin of 3 mm was added to the CTV for lung and 7 mm for prostate [ 45 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the CK plans with the synchrony tracking system, the CTV–PTV margin varied between 0 and 5 mm. MLC tracking on conventional linear accelerators was used in three studies [ 45 , 57 , 61 ]. A margin of 3 mm was added to the CTV for lung and 7 mm for prostate [ 45 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A margin of 3 mm was added to the CTV for lung and 7 mm for prostate [ 45 , 57 ]. Using an MR-linac with an online re-planning feature, only a 1‑mm margin around the CTV was applied [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a planning study by Willigenburg et al [39] showed that single fraction 19 Gy treatment of recurrent prostate cancer may be feasible using the MR-Linac. In this study, 30 patients were included using a 1 mm PTV margin and target dose coverage on the MR-Linac plans was achieved in 57% of the patients.…”
Section: Dose Escalationmentioning
confidence: 99%
“…MR-Linac is feasible if combined with real-time motion mitigation strategies. In addition, Willigenburg et al [39] has shown the feasibility of single fraction 19 Gy MR-Linac treatment for recurrent prostate cancer. The benefit of the MR-Linac in this case may be that ultra-hypofractionation can be delivered without any invasive procedure (fiducial markers, bladder catheter, rectal probe, balloon and/or rectal spacer).…”
Section: Chaptermentioning
confidence: 99%